The economic contribution of tobacco production and marketing models in the development of Zimbabwe - Bwenje, Clemence Taderera (2017)
Agriculture is central to Zimbabwe’s economic recovery and prosperity. The sector however continues to face sustainability, productivity, market access and competiveness challenges. The adoption of tobacco contract farming models in other enterprises has high potential to turnaround agriculture. This study used mixed research methodology to compare economic contributions of tobacco production and marketing models and assess scope for successful transfer of tobacco’s successes to alternative enterprises as part of a broader agriculture intensification agenda. The study concluded that tobacco contract farming models are viable and profitable but their potential to further the agriculture intensification agenda depends on how they are regulated to achieve economic and social equity across groups defined by farm level characteristics. The study recommends intensification of tobacco production and trade to cash-in on increasing global demand; and diversification to alternative enterprises through policies, plans, projects and programmes informed by the experience and circumstatnces of contract tobacco models.